Bridal decoration of the effigy - Mumbai Archive Project Team (Jio Institute, 2024)
Specific bridal items such as the mangalsutra (an auspicious thread worn as a necklace), a new Nauvari saree (a nine-yard saree worn by Koli women), and glass bangles are also placed on the effigy.